2020
DOI: 10.3389/fcimb.2020.00193
|View full text |Cite
|
Sign up to set email alerts
|

Babesia microti Confers Macrophage-Based Cross-Protective Immunity Against Murine Malaria

Abstract: Malaria and babesiosis, the two primary intraerythrocytic protozoan diseases of humans, have been reported in multiple cases of co-infection in endemic regions. As the geographic range and incidence of arthropod-borne infectious diseases is being affected by climate change, co-infection cases with Plasmodium and Babesia are likely to increase. The two parasites have been used in experimental settings, where prior infection with Babesia microti has been shown to protect against fatal malarial infections in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 98 publications
(120 reference statements)
0
18
1
Order By: Relevance
“…In this context, genome plasticity of Leishmania spp. with frequent copy number variations of genes or chromosomes, as well as recombination events, increases their diversity and biological capacity to expand under different stress conditions 33 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, genome plasticity of Leishmania spp. with frequent copy number variations of genes or chromosomes, as well as recombination events, increases their diversity and biological capacity to expand under different stress conditions 33 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Both cellular and humoral immune responses are significantly induced during Babesia and Plasmodium infection. Antibodies block Plasmodium merozoite invasion of erythrocytes; however, they do not appear to significantly promote opsonophagocytosis of iRBCs of either Babesia or Plasmodium ( Moreau et al., 2015 ; Arora et al., 2018 ; Akter et al., 2019 ; Kochayoo et al., 2019 ; Oyong et al., 2019 ; Efstratiou et al., 2020 ). Therefore, humoral immunity appears to play a minor role in resolving the parasitemia of these parasites.…”
Section: Discussionmentioning
confidence: 95%
“…Antibody participation is not essential for offering cross-protection against other hemoparasites. Infection of mice with B. microti could protect mice against a follow-up fatal infection by B. rodhaini ( Efstratiou et al., 2020 ) by reducing parasitemia levels. Surprisingly, significant reduction in the level of antibodies was observed in the protected mice, and levels of cytokines including IFNγ, IL-2, IL-8, IL-10, and IL-12, and of nitric oxide after infection with B. rodhaini also diminished.…”
Section: Immunity Against These Two Protozoan Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been suggested that proinflammatory cytokine activation and erythrocyte adhesion in babesiosis are similar to malaria (Krause et al, 2007;Figure 2B). Some studies have even documented that prior infection with B. microti protects against fatal malaria in mice and primates through a mechanism of cross-protection (van Duivenvoorde et al, 2010;Efstratiou et al, 2020).…”
Section: Immune Response Against Babesiamentioning
confidence: 99%